Analisis Kepuasan Konsumen Menggunakan Metode Algoritma C4.5 Berbasis Rapidminer Pada PT. Adeaksa Indo Jayatama - Nisrina, Dian; Kustiyono, Kustiyono (LPPM UNIKA Santo Thomas Medan, 2024)
In the era of globalization and digital 4.0, the development of technology and the internet plays an important role for human survival. PT. Adeaksa Indo Jayatama, as a provider of telecommunications and internet services, seeks to meet consumer needs with the DexaNet product which offers stable internet connections using fiber optic and wireless broadband. This research uses the C4.5 algorithm method and data mining using the RapidMiner platform to analyze consumer satisfaction. The research results show that the factors that influence consumer satisfaction are facilities and infrastructure, trusted providers, responsiveness, service quality, and stable network. The C4.5 algorithm implemented using RapidMiner has proven to be effective in analyzing customer satisfaction and providing valuable insights for the Company in improving service quality and customer satisfaction.